Picturing Ideal Space Through Perfect Moments - Galvin, Vanessa (Common Ground Publishing LLC, 2012)
Characteristic of the ‘taken for granted’ acceptance of the contradicting relation between the authentic human occupation of space and the form of its pictorial depiction is the normalized erasure of the human trace in depictions of spatial environments. This runs counter to the subjective knowledge of living environments, and is dismissive of the crucial relation between spatial design and its essential purpose. This paper will argue that ideal spatial depictions are representative of an illusory relation to reality, signified in part by the exclusion of the authentic human element in photographic depictions of spatial environments represented in the print media. An alternative representational form of the “perfect moment” in Jean Paul Sartre’s novel “Nausea” (1938), will be used as a tool to juxtapose the sterile quality of the photographic spatial depiction. The nature of and human relation to these differing forms will be compared and contrasted, with the intention of enabling a greater understanding of the conventional desire for spatial ideality, and how this notion of the ideal relates to the expression of the human trace.